Fire protection in homes for the elderly and infirm persons - Miličić, Ana; Benić, Božidar; Brailo, Paula (Crisis Management Days, 2024)
Homes for the elderly and the infirm are intended for housing people who, due to their age and/or various progressive diseases and conditions, have mostly limited and reduced mobility, and their cognitive and motor abilities are greatly reduced. Given the number of people housed in such homes, and their their reduced mobility, homes for the elderly and infirm require specific measures to ensure their safety in the case of any unwanted event, especially in the case of fire. Specific fire protecion measures are related to specifity of the building itself, type of the building, the fire protection systems that should be present in such buildings and the training of personnel to act in emergency situations. In order to achieve adequate protection and safety of the users and wards accommodated in the homes, in relation to the potential danger of fire break out in any part of the building, it is necessary that all the factors mentioned above work together correctly. Fire protection measures in homes for the elderly and infirm in the Republic of Croatia are generally regulated by the Law on Fire Protection and the Ordinace on Fire Resistance and other requirements that building must meet in the case of a fire. Since there is no special domestic rulebook in the field of fire protection that would regulate this issue, foreign guidelies such as the American NFPA 101 Life Safety Code or the Austrian TRVB N 132 are used in accordance with the mentioned regulations. It successfully complements the current national laws and regulations. The aim of this paper is to determine whether homes for the elderly and infirm in the area of Dubrovnik-Neretva County meet all the previously mentioned specific fire protection measures. Qualitative and quantitative research methods will be used in the work. The methodology used in this paper consists of an analysis of the regulations that regulate the area of ​​fire protection in homes for the elderly and infirm and their implementation on the example of homes in the area of ​​Dubrovnik-Neretva County. For the purposes of this paper, a survey was conducted on a conveniet sample, which included public and private homes for the elderly and infirm in the area of Dubrovnik-Neretva Couty, in order to determine the actual situation. The survey qouestionnaire that was sent to homes for the elderly and infirm in Dubrovnik-Neretva County consisted of sixteen questions, the aim of which was to determine the presence of fire protection measures trough all three aspects – the building itself, the implemented systems and the readiness of the staff. The statistical processing of the collected data did not confirm the hypothesis that majority of homes for the elderly and infirm in the area of Dubrovnik-Neretva County meet fire protection conditions. Only one out of thirteen homes located in the area of Dubrovnik-Neretva County generally meets basic requirements for fire protection. One of the homes did not provide data, while other eleven homes provided data from which is visible that most of them do not meet the basic conditions of the building itself, available fire protection systems nor the trained staff. The purpose of this research was to gain a better insight into the issue and if the hypothesis is not confirmed, as it is the case here, to recognize the risks and propose necessary measures so that the basic conditions for the safety of the elderly and infirm accommodated in homes can be fully satified over time, in order to increase their security. For the correction of certain measures, it is necessary to carry out certain interventions in buildings itself with additional adequate financial investments. However, some of the measures, such as trained personnel, do not require any additional financial resources and they can be implemented relatively easily and quickly with appropriate education and professional support.